Placing Intentional Communities in Geography. Issue 5 (3rd September 2019) - Lopez, Christina; Weaver, Russell
Abstract: This article situates intentional communities (ICs) in the discipline of geography, and outlines an agenda for further research into the geographies and experiences of ICs, insofar as such spaces may inform future strategic responses to the complex, multiscalar problems that characterize the Anthropocene. The article introduces readers to different definitions of ICs; presents a typology of ICs; explicitly connects selected meanings, histories, and goals/missions of ICs to both Pattison's geographic research traditions and outstanding "big" questions in geography; highlights selected examples of geographic research on ICs; and sketches a rough agenda for geographic research on and pedagogical applications of ICs.